ALLOCATION OF FINANCIAL RESOURCES TO BUSINESS SECTOR IN UZBEKISTAN (International Journal of Innovative Technologies in Economy, 2018)
Today significant amount of country’s budget is being allocated to develop business climate in Uzbekistan and government is launching large-scale financial support for entrepreneurs, planning projects to provide people who are willing to start their own business acquiring bank loans. Moreover, a lot of privileges are given to female entrepreneurs for their start-up business. The article reviews the allocation of financial resources to small and medium sized enterprises, the role of a banking system in the allocation of money and projects related to development of business sector. Statistics related to the topic is illustrated with graphs and pictures. In the article some ways to develop the business sector are suggested.